Dietary Patterns and A1C in Japanese Men and Women - Nanri, Akiko (American Diabetes Association, 2008)
OBJECTIVE—Dietary patterns in Western populations have been linked to type 2 diabetes, but the role of diet in Japanese remains unclear. We investigated the association between major dietary patterns and glucose tolerance status as measured by A1C in Japanese adults. RESEARCH DESIGN AND METHODS—The groups of subjects were comprised of 3,243 men and 4,667 women who participated in the baseline survey of an ongoing cohort study on lifestyle-related diseases in Fukuoka, Japan. Dietary patterns were derived by using principal-component analysis of the consumption of 49 food items, ascertained by a food-frequency questionnaire. Logistic regression analysis was used to estimate sex-specific odds ratios (ORs) of elevated A1C (≥5.5%), with adjustment for potential confounding variables. RESULTS—The Westernized breakfast pattern characterized by frequent intake of bread but infrequent intake of rice was inversely related to A1C concentrations (P(trend) = 0.02 in both men and women); the multivariate-adjusted ORs for the highest versus lowest quintiles were 0.60 (95% CI 0.43–0.84) and 0.64 (0.46–0.90) for men and women, respectively. The seafood dietary pattern was positively associated with A1C concentrations in men only (P(trend) = 0.01). Neither the healthy nor high-fat dietary pattern was related to A1C. CONCLUSIONS—A dietary pattern featuring frequent intake of white rice may deteriorate glucose metabolism in Japanese men and women, and the salty seafood dietary pattern may have a similar effect in men.